Pengaruh Model Problem Based Instruction Dipadu dengan Teknik Probing Prompting terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Kognitif - Siskayanti, Wahyu Dewi; Nurhidayati, Siti; Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Based on the results of observations and interviews at MTs. NW Pengadang found that students' absorption in biology subjects was still lacking. This study aims to determine the effect of the Problem based instruction model combined with the Probing Prompting technique on critical thinking skills and cognitive learning outcomes of class VII MTs Biology students NW Pengadang for the 2017/2018 school year. The population of this study were all seventh grade students in the even semesters of MTs. NW Pengadang for the 2017/2018 school year. The samples in this study were students of class VII A as the experimental class using the Problem based instruction model with the Probing Prompting technique and class VII B students as the control class using the lecture and discussion method. Collecting critical thinking ability data using tests in the form of description questions. Measurement of students' cognitive learning outcomes using multiple-choice tests. The data analysis technique used descriptive statistics, namely the One Way ANOVA test with a significant level of 5%. Based on the results of the research on critical thinking skills, the control class has an average score of 53.24 in the less critical category, the experimental class has an average value of 67.18 in the critical category, the cognitive learning outcomes of the control class have an average value of 77, the experimental class has an average value 78.14. The results of hypothesis testing using One Way ANOVA with the help of SPSS stated that critical thinking ability has a value of > = 21,298 > 4,030 and for cognitive learning outcomes it has a value of > = 8,991 > 4,030. The results of the study can be concluded that: There is an effect of the Problem Based Instruction model combined with the Probing Prompting technique on the critical thinking ability and cognitive learning outcomes of the VII grade MTs Biology students NW Pengadang for the 2017/2018 school year.